2015
DOI: 10.1016/j.jedc.2014.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Inferring monetary policy objectives with a partially observed state

Abstract: a b s t r a c tAccounting for the uncertainty in real-time perceptions of the state of the economy is believed to be critical for monetary policy analysis. We investigate this claim through the lens of a New Keynesian model with optimal discretionary policy and partial information. Structural parameters are estimated using a data set that includes real-time and ex post revised observations spanning 1965-2010. In comparison to a standard complete information model, our estimates reveal that under partial inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 86 publications
0
3
0
Order By: Relevance
“…The estimation problem is computationally reasonably straightforward, but time consuming since we have to solve a linear-quadratic dynamic programming problem and a linear rational expectations model every period for every draw. 18 5 Estimation Results Figure 3 shows the marginal posterior distributions for each parameter that we estimate,…”
Section: Likelihood Function and Bayesian Inferencementioning
confidence: 99%
“…The estimation problem is computationally reasonably straightforward, but time consuming since we have to solve a linear-quadratic dynamic programming problem and a linear rational expectations model every period for every draw. 18 5 Estimation Results Figure 3 shows the marginal posterior distributions for each parameter that we estimate,…”
Section: Likelihood Function and Bayesian Inferencementioning
confidence: 99%
“…Chen et al (2017b) showed in a DSGE set-up that the conservatism regarding inflation targeting by the US Fed decreased substantially during times of financial turbulence. Givens and Salemi (2015) used a similar DSGE set up to show that the central bank's uncertainty regarding state of the economy in the real time, plays an important role under discretionary policy regime. In particular, the inferred policy stances evolve substantially over time.…”
Section: Indian Institute Of Management Ahmedabad -380015 India 1 Introductionmentioning
confidence: 99%
“…Additionally, they assess the output gap inflation tradeoff facing the ECB. Givens and Salemi (2015) estimate an NK model with optimal discretionary policy using real-time and ex-post US data for the 1965-2010 period.…”
Section: Introductionmentioning
confidence: 99%